MODIFIED POSTERIOR SAGITTAL ANO-RECTOPLASTY: A NEW APPROACH FOR THE MANAGEMENT OF ANO-RECTAL MALFORMATIONS IN CHILDREN - Khan, Kifayat; Khan, Muhammad Younas; Mamoon, Muhammad; Manan, Fazal; Uzair, Muhammad; Fayaz, Muhammad; Hussain, Musarrat; Rahim, Saddar; Tariq, Muhammad (Journal of Postgraduate Medical Institute, 2012)
Objectives: To introduce a technical modification in Posterior Sagittal Ano-rectoplasty (PSARP), commonlyknown as Pena's procedure, and to analyse the outcome of such modified procedure in terms of fecalcontinence and other relevant complications in children with ano-rectal malformations. Methodology: It was a prospective and descriptive study, conducted at thefrom January 2004 to December 2006. Forty patients were studied. Allchildren of either sex with ano-rectal malformation who presented first to our department were included inour study excluding others treated some where else. Relevant investigations were performed in all patients.Diverting colonic or small bowel stoma was created in all patients at presentation to our department. Thetechnique was performed at or after six months of age, depending upon the clinical condition of thepatient. After discharge, all patients were examined and monitored in the out-patient department over aperiod of two years. Results: Out of 40 patients 25(62.5%) were male and 15 (37.5%) were female age range from 6-12months. On 35 (87.5%). Isolated PSARP while on 5 (12.5%) patients modified PSARP with abdominalapproach were performed. Anal stenosis was found in 3(7.50%) patients, rectal mucosal prolapse in4(10%), faecal soiling and faecal incontinence in 17(43.58%) and 7(17.05%) patients were respectively.Faecal continence was good, fair and poor in 15(38.46%), 17(43.58%) and 7(17.94%) patientsrespectively. Conclusion: Our results of the present series suggest that this procedure is a valuable alternative toPSARP for the treatment of anorectal malformations.